Non-radical pathway dominated highly efficient degradation of norfloxacin using persulfate activation with iron-based biochar - Congcong WANG; Jiawei CHEN (Shuiwen dizhi gongcheng dizhi, 2024)
In recent years, the removal of new pollutants has been widely concerned. The antibiotic norfloxacin, a typical emerging contaminant, is capable of concentrating in large quantities in the soil and threatening human health. It has been shown that among many removal means, the activation of strong oxidants by iron-based biochar is an efficient and inexpensive in-situ removal method. The content, valence, and loading of iron are the key factors affecting the catalytic activity; however, how to maximize its removal capacity has not been explored yet. This study systematically investigated the effects of pyrolysis temperature and biomass particle size of iron-based biochar on the efficient removal of norfloxacin, a typical antibiotic in soil. The degradation efficiency and capacity of different iron-based biochar for norfloxacin were obtained using batch experiments; the key mechanisms of norfloxacin degradation were explored by free radical quenching experiments combined with multiple characterizations. The results show that the iron-based biochar prepared at 900 °C pyrolysis temperature and small biomass particle size (75～150 μm) exhibit the best removal efficiency and is able to degrade norfloxacin completely within 10 min. Furthermore, it can maintain a 50% degradation capacity after three times use. The mechanism analysis indicates that the non-radical pathway dominates this degradation process by singlet oxygen, while the sulfate and hydroxyl radicals play auxiliary roles. The catalytic oxidation system constructed in this study has high degradation efficiency of norfloxacin, high applicability to environmental pH, and low risk of secondary contamination. It is expected to be used for the remediation of norfloxacin-type contamination in the soil.